Atarashii Kaze's New Public Diplomacy (AJIKAZE) Toward Indonesia in 2019-2024 - Patra, Bunga Hafizza; Rahman, Junita Budi; Purnama, Chandra (Green Publisher Indonesia, 2025)
This research focuses on the analysis of public diplomacy conducted by Atarashii Kaze (Ajikaze) in Indonesia as a form of promotion of Japanese culture. Public diplomacy is one of the important strategies in international relations, especially in building positive relations between the Japanese and Indonesian people. The conceptual framework of this research uses the theory of public diplomacy activities proposed by Nicholas J. Cull, which includes elements such as listening, advocacy, cultural diplomacy, exchange diplomacy, and international broadcasting. This research was conducted using a descriptive method with a qualitative approach to explore the activities and forms of public diplomacy carried out by Ajikaze. The study results show that Atarashii Kaze's public diplomacy in Indonesia is implemented through a series of activities, such as exchanges through programs (I-mate), cultural visits, and the organization of various events that allow the target audience to actively participate in the cultural experience.